2008
DOI: 10.1002/cncr.23885
|View full text |Cite
|
Sign up to set email alerts
|

Percent free prostate‐specific antigen (PSA) is an accurate predictor of prostate cancer risk in men with serum PSA 2.5 ng/mL and lower

Abstract: BACKGROUND.Up to 17% of men with a prostate‐specific antigen (PSA) level below the accepted prostate biopsy cutoff of 2.5 ng/mL may have prostate cancer. Because identification of these patients represents a difficult task, we assessed the ability of percent free PSA to discriminate between benign and malignant prostate biopsy outcomes in men with PSA ≤2.5 ng/mL.METHODS.Between 1999 and 2006, 543 men with a PSA ≤2.5 ng/mL were referred for initial prostate biopsy. Age, total PSA, percent free PSA, and digital … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
4

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 32 publications
(38 reference statements)
0
15
0
4
Order By: Relevance
“…A further indication of the intrinsic safety of all forms of TRT was that with each preparation, the free PSA increased in proportion to the total PSA, so that the free/total ratio remained constant or increased with treatment (Table 2). Published studies indicate that a low ratio can indicate an increased risk of PCa, and may be a useful clinical index for PCa [14,15]. In this study, some reduction in this ratio was observed in those cases that developed PCa, changing from 0.23 to 0.17 between presentation and the time of diagnosis.…”
Section: Resultsmentioning
confidence: 46%
“…A further indication of the intrinsic safety of all forms of TRT was that with each preparation, the free PSA increased in proportion to the total PSA, so that the free/total ratio remained constant or increased with treatment (Table 2). Published studies indicate that a low ratio can indicate an increased risk of PCa, and may be a useful clinical index for PCa [14,15]. In this study, some reduction in this ratio was observed in those cases that developed PCa, changing from 0.23 to 0.17 between presentation and the time of diagnosis.…”
Section: Resultsmentioning
confidence: 46%
“…In addition, tumor cells are known to secrete soluble proteins [27, 85, 86] and antigen carrying exosomes [87, 88]. However the form of tumor antigen that is captured by DCs for cross-presentation is not known.…”
Section: What Is the Source And Form Of Tumour Antigen For Cross-pmentioning
confidence: 99%
“…Management of cases may be apparent provided that PSA levels are markedly over or below the cutoff value, but the state that PSA values are around the cutoff value has been a challenge for urologists [6, 7]. In such conditions little changes of PSA or its derivatives, produced by hidden factors related to either biological variation of PSA or laboratory analysis, may have inevitable effect on selecting patients for prostate biopsy [8, 9].…”
Section: Introductionmentioning
confidence: 99%